Integration of Knowledge (IoK) Methodological Reasoning of Islamic Economics (IE) as the Wisdom of Humanity: A Heterodox Economic Approach - Omercic, Jasmin (Universitas Muhammadiyah Yogyakarta, 2021)
The world increasingly needs an alternative approach to economic development. This paper endorses the Integration of Knowledge (IoK) approach as the wisdom of humanity through Islamic Economics (IE). A review of relevant literature through qualitative methodologies of library research, discourse and critical content analysis highlights the civilisational practices of integration, how development of economics diverged from such practices and how heterodox approaches reacted to such divergence. A section on learning the wisdom of humanity from each other emphasizes the inevitable historical civilizational integration (IoK) and exchange of knowledge. It follows with a literature review of the development of mainstream economics, how it abandoned such historical civilizational practice and its sound foundations, namely ontology, epistemology, axiology and methodology. A highlight of heterodox economics (HE) responses reveals the alternatives to the mainstream-focused positivistic approach to economics. The inadequacy of those alternatives led us to demonstrate Muslim responses and the centrality of IE as a comprehensive alternative heterodox economic approach. The analysis shows how IE grew along Islamisation of Knowledge (IOK) as two parallel and major intellectual iṣlaḥ (reform) and tajdīd (renewal) movements. A brief review of the development of each shows the potential of IE’s IoK methodological reasoning to revive the IoK approach in economics as the wisdom of humanity. The sound IE philosophical foundations, namely ontology, epistemology, axiology and methodology, have a major impact in that process. Thus, utilising the core IoK objective within IOK together with IE contributions shape the process of overcoming problems and issues of mainstream economics. Actionable recommendations to practitioners and academics depict how the IE approach to economics could be implemented and sustained along SDGs agenda.